THE DOCTRINE OF „NON – DISCLOSURE‟ UNDER THE LAW OF INSURANCE: A CRITICAL APPRAISAL - Jejelola, O. J. (European Scientific Journal, ESJ, 2014)
The subject of insurance law has been a very trickish and clumsy one to anybody who desires to know about it or conduct any research with regard to same. The general notion of the public against insurance companies is very negative when it comes to the aspect of payment of indemnity by the insurers. Perhaps based on a simple or very trivial excuse, the insurer may repudiate liability either on the basis of non – disclosure or non – possession of insurable interest e.t.c. In most cases, insurers have denied or repudiated indemnities on ground of non – disclosure which in all of the policies are made to be a ―warranty‖ or ―conditions‖ which goes to the root of the contract itself. The common law rule on this is very strict and therefore operates against the claim of the assured whenever the defence is raised by the insurer. However, the Nigerian Insurance Act, appears to have remedied this common law position by making the concept of non – disclosure equitable to both parties to an insurance policy. It is hereby suggested that other jurisdiction should follow suit for the development of insurance law.